(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
Blockchain technology is revolutionary. Blockchain Technology will bring revolution within the areas of accounting, e-Government, Finance, BPM, insurance, amusement, trading platforms, healthcare, Internet-of-Things, further as law corporations. Blockchain Technology includes a vast potential in introducing innovative solutions, reckoning on the realm or the world of its implementation, since economic potency and social advantages may be achieved through technical innovation and applications.